STUDY ON THE SUSTAINABILITY OF THE USE OF ANTIMICROBIAL (AMU) AND ANTIMICROBIAL RESISTANCE (AMR) IN MARINE FISH FARMING IN THE BAY - Syaripuddin; Bethsy J Pattiasina; Shelly M Pattipeiluhu (Jurnal Ilmu Pendidikan Indonesia, 2025)
Abstract: Use of antibiotics and chemicals substances were done to prevent bacterial attacks especially byVibrio sp, which if used excessively will cause bacterial resistance. Another problem that arises is the risk ofdamage to the surrounding environment of fish farming and human health, therefore the use of thesesubstances must be effective and efficient. The research aims to determine the antimicrobial inhibition duringthe handling of cage-cultured fish diseases and to determine the level of resistance to antimicrobialsubstances (Antimicrobial Resistance/AMR) to obtain recommendations for the sustainability ofantimicrobial use. Disk diffusion test method with antibiotics Oxytetracycline, Enrofloxacin, andTetracycline in paper disc form was used in the inhibition test. Bacterial identification used biochemical testswith bacterial culture media (TCBS) also biochemical tests using the API 20E kit. The results show that theinhibitory power of using the three types of antibiotics is able to provide sensitive and intermediate responsesto Vibrio sp bacteria. Sensitivity inhibition in white snapper, trevally, grouper, and humpback grouper withoxytetracycline antibiotics all at 60%, enrofloxacin antibiotics respectively 80%, 100%, 100%, and 80%;and tetracycline antibiotics respectively 60%, 100%, 60%, and 80%. Intermediate inhibition with the samegroup of fishes with oxytetracycline antibiotics all at 40%, enrofloxacin antibiotic in all fish 0%, except inhumpback grouper 20% and tetracycline antibiotics respectively 40%, 0%, 40%, and 20%. Thus, it can beconcluded that the use of oxytetracycline, enrofloxacin, and tetracycline antibiotics can still be recommendedfor the management of diseases in aquaculture. For common bacteria, two types of bacteria Vibrioparahaemolyticus and Vibrio alginolyticus have been found.Keywords: Resistance, Vibrio spp, antibiotics, fish farming